GROWTH PROCESS OF ORGANIC VETIVER ROOT WITH POTATO AS INTERCROPPING PLANT - Kadarohman, Asep; Eko S., Ratnaningsih; Dwiyanti, Gebi; Lailatul K., Lela; Kadarusman, Ede; Nur F., Ahmad (AGRIVITA, Journal of Agricultural Science, 2012)
Vetiver oil (Vetiveria zizanoides) is one of Indonesia main export commodities. Vetiver root is perennial plant and generally planted with vegetables as intercropping plant. Increasing the selling price of vetiver oil can be done by transferring the production of conventional vetiver oil (non-organic) to organic vetiver oil. Demonstration of land used was one hectare, which 2,000 m2 for planting vetiver root with potato (Solanum tuberosum) as inter-cropping plant and 8,000 m2 for vetiver root without intercropping, in Sukakarya-Samarang, Garut. The planting used goat and cow dung as manure, distillate water of vetiver oil and liquid bio-pesticide as pesticide. Variables studied included plant height, number of leaf and crotch. In the first quarter of the years, the number of leaf and crotch of vetiver root with intercropping was better than vetiver root without inter-cropping. However, there was not significant difference for plant height of vetiver root, both with and without intercropping. Products of organic potato as intercropping plant of vetiver root were less than those of non-organic potato, but the latter had a better texture and durability. Â  Keywords: Vetiveria zizanoides, Solanum tube-rosum, intercropping, organic farming